An exceptionally rare case and literature review of concomitant duplicated inferior vena cava, renal malrotation, intestinal malrotation, May-Thurner anatomy, and papillary renal cell carcinoma - Yonathan William; Patricia Jorisal; Marto Sugiono; Shintia Christina; Gilbert Sterling Octavius (The Egyptian Journal of Radiology and Nuclear Medicine)
Abstract Background Duplicated inferior vena cava (IVC) is a rare anatomical anomaly typically identified incidentally during imaging or surgery. While usually asymptomatic, it poses significant surgical challenges, particularly during nephrectomy. Concurrently, renal malrotation, intestinal malrotation, and May-Thurner anatomy are infrequently observed. The combination of these anomalies with papillary renal cell carcinoma has never been documented, underscoring the unique nature of this case. Case presentation We present the case of a 56-year-old male patient with abdominal bloating and a palpable mass. Imaging revealed a Bosniak category 4 cystic renal mass, subsequently diagnosed as papillary renal cell carcinoma, alongside duplicated IVC, malrotation of the left kidney and intestines, and May-Thurner anatomy. CT venography confirmed compression of the left IVC and iliac veins by the renal mass and calcified vessels. The patient underwent a successful radical nephrectomy with careful preoperative planning to mitigate risks associated with these anomalies. Postoperative recovery was uneventful, with complete resolution of symptoms. Conclusion This case illustrates a highly rare convergence of anatomical anomalies and malignancy, emphasizing the critical importance of meticulous preoperative imaging and surgical planning.